Effect of Supportive Leadership Style and Teamwork on Employee Productivity - Muh. Khaddafi; Ilham; Muhammad Irvan; Elisha Sunijati; Martinus Tjendana (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The purpose of this study is to provide theoretical understanding from experts regarding the effect of supportive leadership style and teamwork on employee productivity. This theoretical understanding from experts is part of qualitative research that uses complementary sources from books and journal articles. The research results show that the effect of supportive leadership style and teamwork on employee productivity is one of the most researched topics in human resource management and organizational behavior. Experts agree that the combination of supportive leadership style and solid teamwork creates a positive work environment that directly boosts employee productivity. The implementation of a supportive leadership style combined with solid teamwork plays a crucial role in boosting employee productivity in the modern workplace. Based on this, the main recommendation that management can implement is to build a culture of inclusive two-way communication and actively provide space for employee development. Leaders should no longer simply act as rigid supervisors, but rather position themselves as mentors who are sensitive to the personal and professional challenges faced by their team members.